International Direct Marketing Principles, Best Practices, Marketing Facts - Krafft, Manfred.; Krafft, Manfred.; Hesse, Jürgen.; Hesse, Jürgen.; Höfling, Jürgen.; Höfling, Jürgen.; Peters, Kay.; Peters, Kay.; Rinas, Diane.; Rinas, Diane. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Direct marketing is a fast-growing and dominant domestic marketing instrument in many countries. Direct marketing follows the path of the rapid advances of globalization: international direct marketing (IDM) is already a multi-billion dollar business and an attractive instrument for foreign market entry and international customer communication. This book is the first to focus exclusively on IDM, combining state-of-the-art knowledge, best practice and unique data: The first part is a comprehensive, well-structured review, covering relevant sources ranging from academic journals to practitioner magazines. The second part consists of best practice examples of various aspects of IDM. The third part contains a summary of a proprietary consumer study on direct marketing attitudes and affinities across 24 countries in North America, Europe and Asia. The book provides the reader with a comprehensive and easy-to-understand guide to international direct marketing. Direct Marketing has now come of age...internationally. The authors define, illustrate and demonstrate that direct marketing can play on a level field with other forms of international and global marketing communication. Packed with relevant examples and illustrated with individual market data, this text is a "must have" for every CMO focused in growing the business outside the home market. Don E. Schultz, Professor of Integrated Marketing Communication, Northwestern University Every marketer intending to cross borders or expand globally should have this book, even if you are already an "old hand" at entering new markets. Astute cultural notes, pertinent and contemporary case studies and solid statistics for individual countries combine to make this an invaluable resource that is truly without precedent. Dr. Ramesh A. Lakshmi-Ratan, Executive Vice President and Chief Operation Officer of the DMA.